Effect of transplanting and direct seeding on seed yield & important agronomic traits in rapeseed (Brassica napus L.) - Valiollah Rameeh (Journal of Oilseed Brassica, 2026)
In order to compare the effect of transplanting and direct seeding methods on rapeseed (Brassica napus L.) in terms ofagronomic traits, seed yield and yield components an experiment was conducted in a factorial arrangement in randomizedcomplete block design with three replications during 2017-18. Investigating factors included rapeseed genotypes Zafar,L22, L17, and Hyola420 and culture methods were transplanting and direct seeding methods. The analysis of variancerevealed significant effect of cultivars on all studied characteristics viz., number of pods on main raceme, number of podsper plant, pod length, number of seeds per pod, 1000- seed weight, seed yield and oil content. The average seed yield ofgenotypes in transplanting and direct cultivation methods was 3114 and 2312 kg ha-1, respectively which were classifiedin two distinct statistical classes. All the traits progressively increased in transplanting cultivation method. Correlationbetween seed yield and yield components were positive and significant indicating a positive and significant effect ofthese traits on seed yield in both cultivation methods.